2019
DOI: 10.1038/s41388-019-0695-8
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal trapping of palbociclib and its functional implications

Abstract: Palbociclib is a selective inhibitor of cyclin-dependent kinases 4 and 6 (CDK4/6) approved for the treatment of some cancers. The main mechanism of action of palbociclib is to induce cell cycle arrest and senescence on responsive cells. Here, we report that palbociclib concentrates in intracellular acidic vesicles, where it can be readily observed due to its intrinsic fluorescence, and it is released from these vesicles upon dilution or washing out of the extracellular medium. This reversible storage of drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 50 publications
4
54
0
1
Order By: Relevance
“…From a therapeutic viewpoint, the enlarged lysosomal compartment offers an increased capacity to trap drugs that can be protonated, such as the selective CDK4/6 inhibitors palbociclib, ribociclib, and abemaciclib. This capacity reduces their effective concentration in the cytosol and nucleus but is counteracted by the slow release of the drugs from the lysosomes, thereby increasing drug exposure time (Llanos et al, 2019). Another senescence trait, related to lysosomal malfunction, is the intra-lysosomal accumulation of lipofuscin aggresomes (see ''Protein Damage'' and ''Lipid Damage'') (as reviewed in Gorgoulis et al, 2018).…”
Section: Deregulated Metabolic Profilementioning
confidence: 99%
“…From a therapeutic viewpoint, the enlarged lysosomal compartment offers an increased capacity to trap drugs that can be protonated, such as the selective CDK4/6 inhibitors palbociclib, ribociclib, and abemaciclib. This capacity reduces their effective concentration in the cytosol and nucleus but is counteracted by the slow release of the drugs from the lysosomes, thereby increasing drug exposure time (Llanos et al, 2019). Another senescence trait, related to lysosomal malfunction, is the intra-lysosomal accumulation of lipofuscin aggresomes (see ''Protein Damage'' and ''Lipid Damage'') (as reviewed in Gorgoulis et al, 2018).…”
Section: Deregulated Metabolic Profilementioning
confidence: 99%
“…To reduce CDK4 activity, we exposed cells to palbociclib, a chemical inhibitor of CDK4/6. At concentrations that exceed 1µM, palbociclib promotes cell cycle arrest (Llanos et al, 2019). For our experiments, we carefully optimized a palbociclib concentration range that decreases CDK4 activity but does not result in cell cycle arrest ( Fig.…”
Section: Cdk4 Activity Determines the Quantitative Relationship Betwementioning
confidence: 99%
“…8 In this study, the chemically related ribociclib was thought to similarly demonstrate lysosomotropic properties. 8 We hypothesize that this process of lysosomal sequestration posits a potential mechanism by which ribociclib may lead to the development of vortex keratopathy.…”
mentioning
confidence: 97%
“…7 A recent study by Llanos et al has demonstrated that palbociclib, another small-molecule inhibitor of CDK4/6, demonstrates the property of lysosomal trapping. 8 The prolonged release of palbociclib from lysosomes may play a key role in its length of inhibition of CDK4/6 and ability to induce sustained cellular senescence. 8 In this study, the chemically related ribociclib was thought to similarly demonstrate lysosomotropic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation